Risk Disclosures in Bank Reporting: Sustainable Finance Roadmap Era - Dosinta, Nina Febriana; Astarani, Juanda (Journal of Accounting Research, Organization and Economics, 2021)
AbstractObjective This research aims to investigate risk disclosures in bank reporting in the era of the sustainable finance roadmap.Methodology This research uses a content analysis approach with 252 annual reports and 85 stand-alone sustainability reports on banks listed on the Indonesia Stock Exchange for 2014-2020.Results The research results indicate that risk disclosures contained in 36 bank reports listed on the Indonesia Stock Exchange in the era of the sustainable finance roadmap as an effort to detect risks and anticipate sustainable finance risks in the annual reports and the stand-alone sustainability reports. In line with the Sustainable Finance Action Plan, the banking companies effort to provide long-term value creation for sustainable competitive advantage and society and environment and strengthening resilience because they have managed all economic, social, and environmental risks.Research Implications Strengthening sustainable finance that focuses on the basic regulatory framework and reporting system by anticipating sustainable finance risks can maintain the company's continuity and improve the community's welfare to support the Government in achieving the Sustainable Development Goals.